2018
DOI: 10.1007/s10854-018-9663-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of platinum contact metallization on Cu/Sn bonding

Abstract: In this work, formation and evolution of microstructures in CuSn/Pt bonding were investigated after 320 °C reflow process as well as after high temperature storage test at 150 °C. Sputtered thin film platinum on silicon wafer and high purity platinum sheet were applied as contact metallizations for electroplated copper-tin based bonding metallurgy. As bonded microstructure showed PtSn4 intermetallic compound growth at the Pt/Sn interface, and both Cu6Sn5 and Cu3Sn phases formed at the Cu/Sn interface. Both hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Nonetheless, this phenomenon can be controlled by stabilizing the HT-hexagonal phase down to room temperature via introducing a third element (such as Ni, Au, In, and Zn) to the Cu-Sn SLID bonding system [16,25,27,29]. For instance, A. Rautiainen et al reported the drastic impact of Pt on the stabilization of HT-hexagonal Cu 6 Sn 5 phase [30]. Nonetheless, in addition to the microstructural evolution and the bond quality, understanding the mechanical behavior of the Cu-Sn SLID system is of utmost importance to design a mechanical reliable bond.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, this phenomenon can be controlled by stabilizing the HT-hexagonal phase down to room temperature via introducing a third element (such as Ni, Au, In, and Zn) to the Cu-Sn SLID bonding system [16,25,27,29]. For instance, A. Rautiainen et al reported the drastic impact of Pt on the stabilization of HT-hexagonal Cu 6 Sn 5 phase [30]. Nonetheless, in addition to the microstructural evolution and the bond quality, understanding the mechanical behavior of the Cu-Sn SLID system is of utmost importance to design a mechanical reliable bond.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, utilizing Cu-Sn SLID bonding for MEMS packaging demands a physically deposited contact metallization layer/stack on the device wafers to avoid wet-process techniques (electroplating of contact metallization for Cu-Sn SLID system) [30,46]. A wide variety of chemically or physically deposited contact metallization layers (such as Cu, Ni, Ag, and Pt) have been used for Cu-Sn SLID bonding systems in the literature [30,[47][48][49][50]. For instance, A. Rautiainen et al discovered a Pt contact metallization layer for Cu-Sn SLID bonding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[29][30][31][32][33][34][35][36][37][38] Au-Sn and Cu-Sn systems have been demonstrated to form mechanically and chemically reliable bonds at bonding temperatures close to 300°C. [39][40][41][42] However, there is only a limited amount of information available on ternary and higher order SLID systems that can provide additional benefits, such as even lower processing temperatures or enhanced physical properties for higher functional performance and long-term reliability. Due to its low melting temperature (T M = 156.6°C) and known compatibility with the commonly used metallizations in electronics, indium has been widely utilized in low-temperature lead free solders.…”
Section: Introductionmentioning
confidence: 99%
“…As a solution to prevent a Cu contamination, mitigating measures—e.g., tantalum diffusion barriers—were proposed . Platinum is often considered as a protection and a diffusion barrier in multilayer contact pads . An understanding of copper–platinum‐related electrically active defects in Si is not only important from a scientific point of view, but it also has some technological relevance.…”
Section: Introductionmentioning
confidence: 99%